"As Expected": Theoretical Implications for Racialized Administrative Power as the Status Quo. (5th March 2022) - Blume, Grant H
Abstract: This article posits that racialized administrative power is the status quo in the United States and results from a wicked problem broadly construed as institutional racism. Acknowledging a baseline reality of racialized administrative power in the United States allows public administration theory to more directly grapple with the institutional racism that paradoxically may seem too big and complex to empirically study yet simultaneously too important and urgent to ignore. This article offers three contributions to the development of public administration theory from this conceptual frame of racialized administrative power as the status quo. First, by conceptualizing institutional racism as a wicked problem, a case is outlined to replace an assumption of neutral administrative power with a baseline assumption of racialized administrative power in the United States. Second, the article explores two prominent areas of theory in public administration—representative bureaucracy and administrative burden—to demonstrate how a baseline assumption of racialized administrative power can reorient and expand theoretical questions and research. Third, the article discusses the epistemological implications for public administration theory and research based on an assumption that racialized administrative power is the status quo. These contributions offer a step forward in addressing the need for public administration theory to better account for the institutional racism that pervades the management and performance of public organizations in the United States.